Long-term endurance exercise decreases antiangiogenic endostatin signalling in overweight men aged 50–60 years. Issue 2 (23rd July 2007) - Brixius, K; Schoenberger, S; Ladage, D; Knigge, H; Falkowski, G; Hellmich, M; Graf, C; Latsch, J; Montie, G l; Prede, G l; Bloch, W
Abstract : Background: Endurance training may decrease the risk of coronary artery disease. It has been speculated that these effects may be due to an exercise-induced stimulation of angiogenesis. The underlying mechanisms are not yet clear. Therefore, using ELISA, we investigated the plasma level of vascular endothelial growth factor (VEGF, angiogenic factor) and endostatin (antiangiogenic factor) in a group of untrained men aged 50–60 years with obesity. Methods: All men were randomised into a "running" group (training 3 times/week, 60 min each, n = 7), a "cycling" group ( training 3 times/week, 90 min each, n = 7) and a sedentary control group ( n = 7). Both training groups worked at moderate intensity (2–4 mmol/l lactate). The intervention had a duration of 6 months. Before and after this period, blood samples were taken from the participants at rest and they underwent a medical investigation. Results: Body mass index (BMI), systolic and diastolic blood pressure, and plasma levels of VEGF and endostatin were comparable in all three groups. Endurance training significantly reduced BMI in both exercise groups (mean (SEM) before v after 29.7 (0.7) v 29.1 (0.6) kg/m2 and 31.1 (0.7) v 30.1 (0.9) kg/m2 for the running and cycling groups respectively) but not in the control group (30.0 (1.0) v 30.2 (0.8) kg/m2 ). Endurance training did not influence VEGF plasma level (before v after 1.3 (0.4) v 1.5 (0.2) ng/ml for the running group; 1.6 (0.3) v 1.5 (0.2) ng/ml for the cycling group; and 2.5 (0.6) v 2.1 (0.7) ng/ml for the control group). Plasma level of endostatin was significantly reduced in both exercise groups (mean (SEM) before v after: 20.9 (1.6 v 17.5 (1.0) ng/ml and 21.3 (1.4 v 18.0 (1.6) ng/ml for the running and cycling groups respectively) but not in controls (19.7 (1.3 v 17.7 (1.1 ng/ml). Conclusions: Endurance training may reduce the antiangiogenic mechanisms in men aged 50–60 years by reducing endostatin plasma level and this may subsequently decrease the risk of cardiovascular disease.